Exposure to television and individual beliefs: Evidence from a natural experiment - Tanja Hennighausen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Does the information provided by mass media have the power to persistently affect individual beliefs about the drivers of success in life? To answer this question empirically, this contribution exploits a natural experiment on the reception of West German television in the former German Democratic Republic. After identifying the impact of Western television on individual beliefs and attitudes in the late 1980s, longitudinal data from the German Socio-Economic Panel is used to test the persistence of the television effect on individual beliefs during the 1990s. The empirical findings indicate that Western television exposure has made East Germans more inclined to believe that effort rather than luck determines success in life. Furthermore, this effect still persists several years after the German reunification.
urn:nbn:de:bsz:180-madoc-327558
Keywords: D78; D83; H89; P39; 330; media; beliefs; East Germany; GSOEP; Fernsehprogramm; Medienwirkung; Leistungsprinzip; Soziale Werte; Neue Bundesländer; DDR